The Problem of (Un)intentionality in Pedagogy –a View From the Pedagogical Point of View - Sanja Živanović; Ranka Perućica; Sonja Kaurin; Bojana Vuković; Olivera Kalajdžić; Slađana Ćalasan (Društvene i Humanističke Studije, 2023)
When we talk about education, we usually mean planned influences that are exerted on the student to develop all his potential on the one hand. On the other hand, the question arises whether there are unintended influences in the education process, whether their outcome is positive or negative, and whether pedagogy also deals with such spontaneous, unintended processes. Therefore, the goal of this research was to examine and analyze the views of pedagogues, associate and scientific-teaching professions on the nature of the influence that is realized within the framework of education. The sample has the characteristics of a deliberate and convenient sample, and it is composed of pedagogues with associate and scientific-teaching titles from two public universities in the Republic of Srpska. The paper used the method of theoretical analysis and descriptive statistics, and of the techniques, the survey technique. The results show that pedagogues, associate, and scientific-teaching professions under education imply a synthesis of intentional and unintentional influences on the student, only a small number of pedagogues consider that the term functional education is inadequate for what it represents and do not give suggestions for its redefinition. The pedagogues think that the (un)intentionality of education is still a current and open question of pedagogy, but not a fundamental one. In the context of the environment, they believe that the family community is a synthesis of intentional and unintentional influence, and the same integrations are not renounced in the institutional environment as well as in the educational activities that took place even in the pre-civilization period. The results can serve as an initial investigation of the phenomenon of (un)intentionality in education and serve as a basis for further quantitatively and qualitatively larger research, but also for the theoretical foundations of all those who in any way discuss the theoretical issues of general pedagogy.